The jellyfish season - Hahn, Mary Downing (New York : Avon, 1992)
When economic reasons cause two families to merge into a crowded household on the Eastern Shore of Maryland, more personal problems exacerbate the tense living conditions.
Booklist.
Horn Book.
School Library Journal.
5.6
4-6
5-8
Keywords: Eastern Shore (Md. and Va.) -- Fiction; Family problems -- Fiction; Eastern Shore (Md. and Va.) -- Fiction; Family problems -- Fiction